PENGUATAN KARAKTER RELIGIUS MELALUI PROGRAM KEGIATAN MENULIS AYAT SUCI AL-QUR`AN SISWA PEREMPUAN DI SMPN 3 KARTASURA - Pricilia Imelida Stefanie; Achmad Muthali'in (Buletin Literasi Budaya Sekolah, 2023)
This study aims to describe how to strengthen the religious character of SMP N 3 Kartasura students by carrying out the habit of writing Al-Qur`an verses for female students when they are experiencing menstruation which is routinely done every Friday. This study uses a descriptive method with a qualitative approach. The subject of this research is addressed to female students. The object taken from this research is the habit of writing the holy verses of the Al- Qur'an. data collection techniques using observation techniques and also documentation. This research instrument uses an interactive model consisting of data collection, data presentation and drawing conclusions. The results of this study indicate that: 1) strengthening character education is carried out continuously between students and teachers through a habituation program, 2) strengthening religious character through the habit of routinely writing Al- Qur`an verses which are routinely carried out every Friday, 3) writing verses The Holy Al-Qur'an is proven to be able to strengthen the religious character of SMP N 3 Kartasura students.